THE ANALYSIS OF THE EFFECTIVENESS OF THE LBL METHOD WITH A FINAL RESULT APPROACH - Dahliana, Anita; Nirmala Santosa, Winnie (Fakultas Kedokteran Universitas Alkhairaat, 2023)
Anatomy and Histology are crucial fields and serve as fundamental subjects in the clinical phase of Medical Education. Without a strong understanding of anatomy and histology, students cannot perform physical examinations, which are essential procedures for diagnosing diseases. The aim of this study is to determine whether the learning before lecture (LBL) method can improve final grades in Anatomy and Histology. This research employed a quasi-experimental design with a non-equivalent control group design. The subjects were students from the Faculty of Medicine at the University of Surabaya, and comparisons were made between different academic years. The first group received traditional teaching methods with active lecturers. The second group underwent the learning before lecture intervention. The research findings indicate that the final grades in both groups had a p-value of <0.05. Learning before lecture had a significant impact on the final examination scores in anatomy and histology for the students. The results of the study demonstrate that the group exposed to learning before lecture showed a significant improvement in their final grades.